2000
DOI: 10.4049/jimmunol.165.2.962
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Inflammatory Protein-1α Is a Critical Mediator of Host Defense Against Invasive Pulmonary Aspergillosis in Neutropenic Hosts

Abstract: Invasive pulmonary aspergillosis is a devastating complication of immunosuppression that usually occurs in neutropenic patients. In this setting, augmentation of the antifungal activity of available immune cells may improve the outcome of the infection. Macrophage inflammatory protein-1α (MIP-1α) is a CC chemokine with potent chemotactic activity for various subsets of mononuclear leukocytes. We therefore tested the hypothesis that the influx of mononuclear cells into the lung in invasive pulmonary aspergillos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
75
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 54 publications
2
75
0
Order By: Relevance
“…CD34 ϩ cell dose influenced neutrophilmacrophage-monocyte reconstitution that plays an essential role for protection from fungal infections. 39,40 As invasive fungal infection occurs later after BMT, secondary neutropenia, rather than early neutrophil engraftment, is an important risk factor that might also explain the higher fungal infection rate in patients receiving a lower CD34 ϩ cell dose. Finally, the main cause of transplantation-associated death was infection (24 of 53 deaths during the first 180 days after transplantation), with a higher infection-associated mortality rate in patients receiving a lower CD34 ϩ cell dose.…”
Section: Discussionmentioning
confidence: 99%
“…CD34 ϩ cell dose influenced neutrophilmacrophage-monocyte reconstitution that plays an essential role for protection from fungal infections. 39,40 As invasive fungal infection occurs later after BMT, secondary neutropenia, rather than early neutrophil engraftment, is an important risk factor that might also explain the higher fungal infection rate in patients receiving a lower CD34 ϩ cell dose. Finally, the main cause of transplantation-associated death was infection (24 of 53 deaths during the first 180 days after transplantation), with a higher infection-associated mortality rate in patients receiving a lower CD34 ϩ cell dose.…”
Section: Discussionmentioning
confidence: 99%
“…Although boosting the antifungal activity of available immune cells has been shown to improve the outcome of invasive aspergillosis in mice (34), similar strategies have not been previously examined in the context of allergic responsiveness to Aspergillus. Further impetus for the present study came from our previous observations that A. fumigatus-sensitized mice lacking CCR2 due to homologous recombination developed severe allergic disease due to their inability to clear conidia from the lung (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies have shown that cytokines such as TNF-␣ and GM-CSF are required for the recruitment of neutrophils in the airways during fungal challenge (36,37). More recently, a significant role for the CXC chemokine macrophage-inflammatory protein (MIP)-2 (MIP-2) and KC (11,38) and the CC chemokine MIP-1 (MIP-1␣/CCL3) (34) in the recruitment of neutrophils and macrophages, respectively, and the clearance of conidia from the airways was revealed. Much of the data described above are pertinent to models of invasive aspergillosis characterized by fungal colonization in immunodeficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MIP-1␣, a member of the ␤-chemokine subfamily, has been described as a modulator of host defense against infection (12)(13)(14)(15). The absence of MIP-1␣ greatly impairs the recruitment of monocytes and neutrophils into infected organs (12)(13)(14)(15). In addition, MIP-1␣ is able to induce activated macrophages that kill Escherichia coli, Trypanosoma cruzi, or Klebsiella pneumoniae (16 -18) and to be required for the clearance of Cryptococcus neoformans or Listeria monocytogenes in vivo (16,17).…”
mentioning
confidence: 99%
“…In addition, CCR1 (a receptor for MIP-1␣) knockout mice have an increased susceptibility to infection with Aspergillus fumigatus (19). Furthermore, MIP-1␣ augments CTL-and NK-mediated cytolysis (15). These facts have led to the question of whether the impaired ability to produce MIP-1␣ is associated with the increased susceptibility of burned patients to infection.…”
mentioning
confidence: 99%